Assessing Flipped Classroom Techniques for Business Management Education in Bangladesh - Md. Nahid Mia (OUSL Journal)
In the 21st century, Business Management students are becoming increasingly aware of the economic, technological, societal and global market dynamics shaping their fields. In response, educators must adapt to these evolving needs to effectively meet the demands of modern learners. Traditional teaching methods must be updated to foster the higher-order skills that are in high demand by employers. To engage students and cultivate these critical skills, a variety of pedagogical strategies are being implemented. One such strategy is the flipped classroom, which emphasizes application-based learning and active student participation, promoting higher-order thinking skills through a blended learning approach. This study seeks to assess the applicability of the flipped classroom strategy in Business Management classrooms in Bangladesh, ensuring alignment with the country's university curriculum. The research primarily draws on secondary data from various literature sources to explore both the significance and challenges of implementing the flipped classroom approach in Business Management education in Bangladesh. A critical evaluation of current practices highlights their limitations and underscores the potential of the flipped classroom in fostering higher order thinking skills. Additionally, the study presents a lesson plan, and rubrics developed based on the flipped classroom model, informed by the existing literature. The research also identifies potential challenges to implementation and explores how the flipped classroom strategy can support the development of higher-order skills among students. It is anticipated that this study will benefit tutors, academic institutions, education policymakers and administrators in Bangladesh by offering insights and strategies to enhance the employability skills of Business Management graduates.